Mutations in genes encoding regulators of mRNA decapping and translation initiation: links to intellectual disability - Weil, Dominique (Biochem Soc Trans, 2020)
Intellectual disability (ID) affects at least 1% of the population, and typically presents in the first few years of life. ID is characterized by impairments in cognition and adaptive behavior and is often accompanied by further delays in language and motor skills, as seen in many neurodevelopmental disorders (NDD). Recent widespread high-throughput approaches that utilize whole-exome sequencing or whole-genome sequencing have allowed for a considerable increase in the identification of these pathogenic variants in monogenic forms of ID. Notwithstanding this progress, the molecular and cellular consequences of the identified mutations remain mostly unknown. This is particularly important as the associated protein dysfunctions are the prerequisite to the identification of targets for novel drugs of these rare disorders. Recent Next-Generation sequencing-based studies have further established that mutations in genes encoding proteins involved in RNA metabolism are a major cause of NDD. Here, we review recent studies linking germline mutations in genes encoding factors mediating mRNA decay and regulators of translation, namely DCPS, EDC3, DDX6 helicase and ID. These RNA-binding proteins have well-established roles in mRNA decapping and/or translational repression, and the mutations abrogate their ability to remove 5′ caps from mRNA, diminish their interactions with cofactors and stabilize sub-sets of transcripts. Additional genes encoding RNA helicases with roles in translation including DDX3X and DHX30 have also been linked to NDD. Given the speed in the acquisition, analysis and sharing of sequencing data, and the importance of post-transcriptional regulation for brain development, we anticipate mutations in more such factors being identified and functionally characterized.